PENINGKATAN KEMAMPUAN BACA TULIS AL-QUR’AN MAHASISWA PAI MELALUI PROGRAM MATRIKULASI BTQ - Listi Baihati; Santika Lya Diah Pramesti (Universitas Islam Sultan Agung, 2020)
In this study, the author describes the problem of how to implement the BTQ matriculation program at IAIN Pekalongan. Is there an increase in Al-Qur'an literacy skills of PAI students through the BTQ matriculation program at IAIN Pekalongan. The purpose of this study was to determine the implementation of the BTQ matriculation program at IAIN Pekalongan and to find out whether there was an improvement in the Al-Qur'an literacy skills of PAI students through the BTQ matriculation program at IAIN Pekalongan. The approach used in this study is a quantitative approach using experimental methods. The results of the study can be concluded that the implementation of the BTQ matriculation program at Pekalongan IAIN is conducted once a week on Saturdays. To find out the ability of students to read and write the Qur'an, an examination or test is carried out both written tests and oral tests. The results of calculations through prerequisite tests and comparative tests show that the BTQ matriculation program can improve the Al-Qur'an literacy skills of PAI students. From the results of these calculations, it can be concluded that there is a significant increase in the results of student test scores before participating in the BTQ matriculation program and after participating in the BTQ matriculation program.Keywords: Improvement, Read Write Al-Qur'an, BTQ Matriculation Program